Wisconsin Institutes for Discovery - Initial Documents -Raw Data Carl Gulbrandsen - Emon, Ayeshah (My University, 2009)
Files consists of various reports, notes, proposals, agreements, budgets and news articles relating to the construction and development of the Wisconsin Institutes for Discovery dating between 2006-2009. Materials include: Benchmarking (esp. WISTAR and Whitehead Institutes) News articles and clippings Budgets and cost estimations Food Services Cluster Hires Other Project Delivery-Related Materials